2011
DOI: 10.1097/wnr.0b013e32834959c5
|View full text |Cite
|
Sign up to set email alerts
|

A novel calpain inhibitor for treatment of transient retinal ischemia in the rat

Abstract: Following an acute ischemia/reperfusion of the rat retina, the activation of cytotoxic proteases, including calpain, results in necrosis and apoptosis of retinal ganglion cells resulting in their degeneration. Using a systemically administered calpain inhibitor that crosses the Blood-Retinal-Barrier would provide for novel systemic intervention that protects the retina from acute injury and lost function. Here we study a novel calpain peptide inhibitor, cysteic–leucyl–argininal (CYLA), in an in vivo rat model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Interacting with apoptosis and/or autophagy thereby restoring the balance between cell death and cell survival may be a strategy to prevent ERG alterations. For example, in experimental models of retinal damage, inhibiting apoptosis has been shown to prevent visual dysfunction ( David et al, 2011 ; Choudhury et al, 2015 ; Huang et al, 2015 ; Wu et al, 2015 ). In addition, recovering autophagy dysregulation restores ERG in rodent models of retinal diseases ( Kunchithapautham et al, 2011 ; Okamoto et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interacting with apoptosis and/or autophagy thereby restoring the balance between cell death and cell survival may be a strategy to prevent ERG alterations. For example, in experimental models of retinal damage, inhibiting apoptosis has been shown to prevent visual dysfunction ( David et al, 2011 ; Choudhury et al, 2015 ; Huang et al, 2015 ; Wu et al, 2015 ). In addition, recovering autophagy dysregulation restores ERG in rodent models of retinal diseases ( Kunchithapautham et al, 2011 ; Okamoto et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, visual function needs to be assessed under these conditions. Here, sham and tMCAO surgery rats were evaluated for retinal function using ERG measurements collected and analyzed as described previously [32]. In brief, animals were anesthetized and their pupils were dilated with tropicamide and cyclomydril.…”
Section: Methodsmentioning
confidence: 99%
“…An increasing body of evidence suggests that retinal neuron cell death may contribute to the alterations of retinal function. Indeed, it has been observed that inhibiting calpain, a critical mediator of apoptosis, provides significant preservation of retinal function in ischemic rat retina (David et al 2011). In addition, a single intravitreal injection of erythropoietin delays light-induced plotted as a function of stimulus intensity.…”
Section: Electroretinographic Responses and Hypoxia Effectsmentioning
confidence: 98%